Explaining Violence ‐ Towards a Critical Friendship with Neuroscience?1. (9th February 2016) - Ray, Larry
Abstract: The neurosciences challenge the 'standard social science' model of human behaviour particularly with reference to violence. Although explanations of violence are interdisciplinary it remains controversial to work across the division between the social and biological sciences. Neuroscience can be subject to familiar sociological critiques of scientism and reductionism but this paper considers whether this view should be reassessed. Concepts of brain plasticity and epigenetics could prompt reconsideration of the dichotomy of the social and natural while raising questions about the intersections of materiality, embodiment and social action. Although violence is intimately bound up with the body, sociologies of both violence and the body remain on the surface and rarely go under the skin or skulls of violent actors. This article argues for a non‐reductionist realist explanation of violent behaviour that is also interdisciplinary and offers the potential to generate nuanced understandings of violent processes. It concludes that sociology should engage critically and creatively with the neuroscience of violence.